CMMI, is it a new Model or is the CMM evolution? - Ruiz de Mendarozqueta, Álvaro (2002)
This abstract discusses the evolution of the Capability Maturity Model (CMM) into the Capability Maturity Model Integration (CMMI), highlighting its advantages and challenges. ​ The CMM, widely used since the early 1990s, has proven effective in improving productivity, quality, and cycle time in software projects, particularly addressing issues in levels 2 and 3. ​ However, it has limitations, such as ambiguous metrics and lack of coverage in certain areas.